Transformational leadership and prosocial voice behavior: the mediating role of psychological ownership - Ahmad Khoirun Najib; M Shalahuddin; Denny Nabawi; Rahellia Panjaitan (Institute of Computer Science (IOCS), 2026)
Employees were considered critical organizational assets that required professional management to ensure optimal contributions to organizational sustainability and development. One important form of contribution was prosocial voice behavior, defined as employees’ willingness to express constructive ideas, opinions, and suggestions to organizational authorities. Such behavior functioned as a positive indicator of organizational effectiveness, whereas employee silence reflected the opposite condition. Accordingly, identifying factors that fostered prosocial voice behavior was essential. This study aims to examine the effect of transformational leadership on prosocial voice behavior through the mediating role of psychological ownership. The study further explored this mediating mechanism within governance practices of public education institutions, both state-owned and private, in Indonesia. A quantitative cross-sectional design was employed, involving 194 respondents drawn from employees of public and private formal education foundations who had worked for more than one year and were not currently bound by permanent employment contracts with other organizations. Primary data were collected through self-administered online questionnaires. Structural Equation Modeling was applied to test the proposed hypotheses. The results reveal that transformational leadership has a statistically significant and positive effect on prosocial voice behavior. In addition, psychological ownership partially mediated the relationship between transformational leadership and prosocial voice behavior. While previous studies had examined various antecedents of prosocial voice, this study extended the literature by highlighting the role of psychological ownership in the educational sector. The findings offered practical implications for foundations and similar organizations and contributed empirical evidence to the literature on transformational leadership, psychological ownership, and prosocial voice behavior.